Apicomplexan mitoribosome from highly fragmented rRNAs to a functional machine - Chaoyue Wang; Sari Kassem; Rafael Eduardo Oliveira Rocha; Pei Sun; Tan-Trung Nguyen; Joachim Kloehn; Xianyong Liu; Lorenzo Brusini; Alessandro Bonavoglia; Sramona Barua; Fanny Boissier; Mayara Lucia Del Cistia; et al. (Nature Communications)
Abstract The phylum Apicomplexa comprises eukaryotic parasites that cause fatal diseases affecting millions of people and animals worldwide. Their mitochondrial genomes have been significantly reduced, leaving only three protein-coding genes and highly fragmented mitoribosomal rRNAs, raising challenging questions about mitoribosome composition, assembly and structure. Our study reveals how Toxoplasma gondii assembles over 40 mt-rRNA fragments using exclusively nuclear-encoded mitoribosomal proteins and three lineage-specific families of RNA-binding proteins. Among these are four proteins from the Apetala2/Ethylene Response Factor (AP2/ERF) family, originally known as transcription factors in plants and Apicomplexa, now repurposed as essential mitoribosome components. Cryo-EM analysis of the mitoribosome structure demonstrates how these AP2 proteins function as RNA binders to maintain mitoribosome integrity. The mitoribosome is also decorated with members of lineage-specific RNA-binding proteins belonging to RAP (RNA-binding domain abundant in Apicomplexa) proteins and HPR (heptatricopeptide repeat) families, highlighting the unique adaptations of these parasites. Solving the molecular puzzle of apicomplexan mitoribosome could inform the development of therapeutic strategies targeting organellar translation.